Estudo da oxidação a quente no aço inoxidável ferrítico ABNT 430 - Geovane Martins Castro (2005)
The scale, product of the oxidation, is a layer of oxides that is formed on ferritics stainless steels surface during hot processing as reaction with the environment. The oxidation is a metals and alloys change due interaction with the environment. The oxidation reaction is the electrons transfer from the element reducer to the electronic levels free from the element oxidized. Except the Nb, if present in the scale as a carbonitrides, others chemicals elements analyzed by GDLS react with oxygen adsorved. During oxidation, is formed a gradient of concentration of the metals from the surface to the interior of the metal. For that gradient the diffusion occurs in the direction of the surface. The concentration of theelements in the scale is a function of the diffusion coefficient from each one. Concerning to steels performance under oxidation, the type 430E has more oxidation resistance than the type 430A until the temperature of 1050ºC. The niobium addition reduces the oxidation intensity. The oxidation constant K is smaller to the 430E that to the 430A. The thermal activation is the main factor associated to the thickness of the scale.The kinetics of scale growth is almost linear, for the times and temperatures involved in the hot strip mill. Perhaps, this tends to a parabolic behavior with so much time that used in this work.